1988
DOI: 10.1159/000158737
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Vascular Reactivity in Experimental Diabetic Rats: Comparison with Hypothyroid Rats

Abstract: The responsiveness to vasoactive agents in the perfused mesenteric vascular bed of streptozocin-induced diabetic rats was examined and compared with that of propylthiouracil-induced hypothyroid rats. Diabetic rats at 4 and 8 weeks after the induction of diabetes showed a significant decrease in isoproterenol-induced vasodilatation. In addition, the contractile responses to norepinephrine and 5-hydroxytryptamine and the vasodilative response to acetylcholine were significantly decreased in 12-week-diabetic rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 13 publications
4
22
0
1
Order By: Relevance
“…Other workers, also using the in vitro rat mesenteric arterial bed preparation, have shown that sympathetic neuropathy is a consequence of streptozotocin-induced diabetes (Longhurst & Head, 1985;Takiguchi et al, 1988). In these and our study rats were used at a similar time after induction of diabetes; however, in the former studies diabetes was induced in rats weighing (Cracco & Gabella, 1991).…”
Section: Controlmentioning
confidence: 64%
See 2 more Smart Citations
“…Other workers, also using the in vitro rat mesenteric arterial bed preparation, have shown that sympathetic neuropathy is a consequence of streptozotocin-induced diabetes (Longhurst & Head, 1985;Takiguchi et al, 1988). In these and our study rats were used at a similar time after induction of diabetes; however, in the former studies diabetes was induced in rats weighing (Cracco & Gabella, 1991).…”
Section: Controlmentioning
confidence: 64%
“…Furthermore, these results are compatible with those of a recent in vivo study by Kiff et al (1991) who demonstrated raised mesenteric vascular conductance in streptozotocindiabetic rats and no differences in endothelium-dependent vasodilatation to ACh. Attenuated relaxations to endothelium-dependent vasodilators, but generally unimpaired endothelium-independent relaxations have been demonstrated in clinical (De Tejada et al, 1989) and a variety of experimental (Takiguchi et al, 1988;Kamata et al, 1989;Mayhan, 1992;Miyata et al, 1992;Taylor et al, 1992) diabetes, while endothelium-independent relaxations are generally unimpaired. It is possible that diabetes affects the different components of the vasculature with a different time course, with neuropathy occurring before the onset of endothelial changes.…”
Section: Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreases in endothelium-dependent relaxation are a common feature in both conduit 9 -20 and resistance [21][22][23][24][25][26][27][28][29][30] arteries of chemically induced experimental diabetic animals (including rats, mice, rabbits, hamsters, and dogs). In two genetic models of IDDM, similar impaired relaxation has been documented in aorta [31][32][33] and mesenteric arteries 34,35 of diabetes-prone BB/Wor or BB/E rats and in aorta 36 and mesenteric arteries 37 of the diabetes-prone WBN/Kob rat.…”
Section: Impaired Endothelium-dependent Relaxation Experimental Diabementioning
confidence: 99%
“…10 The mechanism of impaired responses of the aorta to /3-adrenergic activation did not appear to be related to an alteration in cAMP, since relaxation of the aorta in response to forskolin was similar in nondiabetic and diabetic rats. 911 Thus, it appears that the mechanism of impaired relaxation of the aorta in diabetic rats in response to activation of /3-adrenergic receptors is related to a decreased density and/or affinity of /3-adrenergic receptors on vascular smooth muscle.…”
mentioning
confidence: 85%